Recognizing and responding to cases of suspected animal cruelty, abuse, and neglect: what the veterinarian needs to know - Arkow P (Dove Medical Press, 2015)
Phil Arkow National Link Coalition – The National Resource Center on The Link Between Animal Abuse and Human Violence, Stratford, NJ, USA Abstract: The identification of a “battered pets” syndrome, which put the veterinary profession on a parallel footing with its counterparts in human medicine who respond to battered children, women, and elders, expanded the veterinarian’s role as an advocate for animals’ welfare to include the recognition of, response to, and prevention of animal abuse. Professional policies and legislation in several nations have been amended to define these responsibilities and delineate appropriate responses when animal maltreatment or other forms of family violence are suspected. This article reviews these changes, discusses abuse as a matter of animal welfare and public health, and summarizes research describing animal abuse as a possible indicator and predictor of interpersonal violence. Five steps that helped build human health care’s response to child abuse, domestic violence, and elder abuse, and that are analogous to forces in contemporary veterinary practice, are described. It familiarizes practitioners with terminology used in animal cruelty investigations. It describes clinical presentations, client profiles and behaviors, and environmental conditions that may raise a practitioner’s index of suspicion of possible animal maltreatment. It reviews protocols that practitioners may employ to respond compassionately and effectively to suspected animal abuse and enhance successful law enforcement investigations and prosecutions. Such responses can unite human and veterinary medicine in a common concern for vulnerable, victimized, and at-risk populations and position veterinarians as an essential part of public health approaches to break the cycles of violence affecting animals and human members of the family and community. Keywords: animal cruelty, animal abuse, neglect, reporting, animal welfare, domestic violence